Association Between Minor Salivary Gland Biopsy During Sjӧgren’s Syndrome and Serologic Biomarkers: A Systematic Review and Meta-Analysis - Berardicurti, Onorina; Ruscitti, Piero; Di Benedetto, Paola; D’Andrea, Settimio; Navarini, Luca; Marino, Annalisa; Cipriani, Paola; Giacomelli, Roberto (Frontiers in Immunology, 2021)
Objective Patients with primary Sjögren’s syndrome (pSS) may develop a potentially severe disease with extra-glandular involvement and lymphoma insurgence. Minor salivary gland biopsy is routinely used in the disease diagnosis, but its potential role as a biomarker for clinical disease presentation and prognosis is still poorly understood. Methods We performed a systematic review and meta-analysis on clinical presentation and prognosis in pSS patients who underwent minor salivary gland biopsy at diagnosis according to the PRISMA guidelines. Results We included five retrospective studies and 589 pSS patients. Ectopic GCs presence was not associated with a significant increase in the odds ratio for the clinical variables explored such as salivary gland swelling, arthritis, and Raynaud’s phenomenon. As far as serological features are concerned, ectopic GCs presence accounted for an increased ratio of antibodies anti-SSA (OR = 3.13, 95% CI: 1.25–7.85, p = 0.02, I2 = 79%), anti-SSB (OR = 3.94, 95% CI: 1.50–10.37, p = 0.0005, I2 = 80%), and RFs presence (OR = 3.12, 95% CI: 1.94–5.00, p < 0.00001, I2 = 0%). Conclusions This study showed that the association between ectopic GC in salivary glands identifies a clinical subset characterized by autoantibodies presence, and probably pSS patients affected from a more severe disease.